2014
DOI: 10.3389/fphy.2014.00074
|View full text |Cite
|
Sign up to set email alerts
|

Rotating structures in low temperature magnetized plasmas—insight from particle simulations

Abstract: The E × B configuration of various low temperature plasma devices is often responsible for the formation of rotating structures and instabilities leading to anomalous electron transport across the magnetic field. In these devices, electrons are strongly magnetized while ions are weakly or not magnetized and this leads to specific physical phenomena that are not present in fusion plasmas where both electrons and ions are strongly magnetized. In this paper we describe basic phenomena involving rotating plasma st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 84 publications
7
94
0
Order By: Relevance
“…We additionally show a potential jump at the head of the zone, which makes the system consistent with the requirement that the plasma potential needs to return to the same value when the path over the racetrack is closed (at same radius r and height z): Ð ðV p ðnÞ À hV p iÞ r;z dn ¼ 0, where hV p i designates the plasma potential averaged of the racetrack. In PIC-MCC (ParticleIn-Cell Monte Carlo Collisions) simulations, Boeuf 65 investigated several E Â B discharge geometries and found that for low pressure discharges, like those investigated here, significant deviations from quasi-neutral conditions can occur suggesting that electron and ion space charge regions are not specific but an essential feature of E Â B discharges.…”
Section: E Comparison Of Potential Measurements With Simulations Fromentioning
confidence: 77%
“…We additionally show a potential jump at the head of the zone, which makes the system consistent with the requirement that the plasma potential needs to return to the same value when the path over the racetrack is closed (at same radius r and height z): Ð ðV p ðnÞ À hV p iÞ r;z dn ¼ 0, where hV p i designates the plasma potential averaged of the racetrack. In PIC-MCC (ParticleIn-Cell Monte Carlo Collisions) simulations, Boeuf 65 investigated several E Â B discharge geometries and found that for low pressure discharges, like those investigated here, significant deviations from quasi-neutral conditions can occur suggesting that electron and ion space charge regions are not specific but an essential feature of E Â B discharges.…”
Section: E Comparison Of Potential Measurements With Simulations Fromentioning
confidence: 77%
“…In the nonlinear regime the perturbed electric field develops into a robust quasi-coherent mode with a pri- mary wave vector around the fundamental cyclotron resonance. 26 The growing mode is driven by the energy input from the few lowest order cyclotron resonances with k 0 providing the dominant contribution, as seen in Fig. 4.…”
Section: Nonlinear Dynamics and Formation Of The Long-wavelengthmentioning
confidence: 94%
“…Alongside these theoretical efforts, computational modelling has become increasingly important in extending present understanding of the spoke. Amongst the many numerical approaches available [31][32][33][34] , simulations employing Particle-in-cell (PIC) codes 33,35 have lately gained relevance, including simulations of real sized devices 36 . Indeed, 'spoke-like' structures have been shown to appear in such recreated devices even in the simplest formulations, such as in the abscence of ionisation or collisions.…”
Section: Introductionmentioning
confidence: 99%